Analysis of Procedural Justice, Distributive Justice, and Group Cohesiveness toward Organizational Loyalty of PT Adhi Karya - Laksmi Sito Dwi Irvianti; Thami Rachmi Larasati (Binus Business Review, 2016)
This research was conducted in PT Adhi Karya, a state company that provides construction services. During the past three years, the company suffered an increasing of employees’ turnover rate because of unappropriate implementaton of procedural and distributive justice in every decision making or applying procedures and rules. Besides that, there were conflicts happened among employees due to the uncohesiveness of groups. The aim of the study was to examine the influence of procedural justice, distributive justice, and group cohesiveness on organizational loyalty. Research method applied was quantitative method. Analysis was done by using multiple regression, in which the data were collected through questionnaires to a sample of 76 people from a total population of 304 people. The result showed that there was a significant effect of procedural justice, distributive justice, and group cohesiveness on organizational loyalty either partially or simultaneously. It may help company in improving the implementation of procedural and distributive justice and group cohesiveness that will lead to higher organization loyalty.